2023
DOI: 10.3389/fmed.2023.1124514
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of protein translation under matrix-deprivation stress in breast cancer cells

Abstract: Matrix-deprivation stress leads to cell-death by anoikis, whereas overcoming anoikis is critical for cancer metastasis. Work from our lab and others has identified a crucial role for the cellular energy sensor AMPK in anoikis-resistance, highlighting a key role for metabolic reprogramming in stress survival. Protein synthesis is a major energy-consuming process that is tightly regulated under stress. Although an increase in protein synthesis in AMPK-depleted experimentally-transformed MEFs has been associated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 89 publications
0
3
0
Order By: Relevance
“…The above experimental data obtained by previous work in our laboratory was used to initiate the development of breast cancer mathematical model. Previously, we also showed that increased levels of pAMPK upon matrix deprivation further leads to a decrease in pAkt 17 and mTOR activity 19 . The calibrated model (Supplementary Fig.…”
Section: The Calibrated and Validated Mathematical Model Captures The...mentioning
confidence: 73%
See 2 more Smart Citations
“…The above experimental data obtained by previous work in our laboratory was used to initiate the development of breast cancer mathematical model. Previously, we also showed that increased levels of pAMPK upon matrix deprivation further leads to a decrease in pAkt 17 and mTOR activity 19 . The calibrated model (Supplementary Fig.…”
Section: The Calibrated and Validated Mathematical Model Captures The...mentioning
confidence: 73%
“…In vitro experimental data, retrieved from previously published work of our laboratory, was used for model calibration and validation. The data included the effects of matrix deprivation on pAkt, pAMPK, p-mTOR, p-S6K1 and metabolism in MDA-MB-231 cells 17,19 . It also consisted the effects of AMPK down-modulation 17 as compared to wild-type condition, upon matrix deprivation.…”
Section: Experimental Data Extractionmentioning
confidence: 99%
See 1 more Smart Citation